Output based bilateral adaptive control of partially known robotic systems. (May 2020) - Castañeda, Luis Ángel; Guzman-Vargas, Lev; Chairez, Isaac; Luviano-Juárez, Alberto
Abstract: This paper describes the design and implementation of a robust adaptive bilateral observer based control to solve the trajectory tracking problem for a class of master–slave robotic systems. The output-based bilateral control uses an adaptive observer to estimate the force and the unmeasurable velocity state considering only the master–slave system order as well as the position measurements. The stability of the observer and controller is simultaneously proved via the second method of Lyapunov. A set of experimental tests proved the performance of the presented algorithm for a manipulation task in a bilateral teleoperated system based on two delta robots. Graphical abstract: Highlights: The bilateral teleoperation for robotic systems is solved using adaptive disturbance estimation. The disturbance adaptive estimation is based on a Least Squares Algorithm. The disturbance is expressed by a time varying combination of the state vector. The second method of Lyapunov is used to show the ultimate bound of the estimation/tracking error. Experimental tests on two parallel robots show the effectiveness of the suggested controller.